Functional regulation of decidual macrophages during pregnancy. (February 2021) - Sun, Fengrun; Wang, Songcun; Du, Meirong
Highlights: Decidual macrophages may originate from both embryonic macrophages and hematopoietic stem cells-derived macrophages in bone marrow. Decidual macrophages possess unique phenotypes different from peripheral macrophages, which alter in different phases of pregnancy. Decidual macrophages play irreplaceable roles in key events of normal pregnancy. Decidual macrophages dysfunction is closely related to pregnancy implications. Abstract: A successful pregnancy requires that the maternal immune system recognizes and tolerates the semi-allogeneic fetus without compromising the capability of protecting both mother and fetus from various pathogens. Decidual macrophages present unique phenotypes to play a key role in the establishment of the immunological aspects of maternal-fetal interaction. Dysfunction of decidual macrophages gives rise to pregnancy complications such as preeclampsia, recurrent spontaneous miscarriage, preterm labor and fetal growth restriction. Here, we reviewed the latest knowledge on the origin, differentiation, unique phenotype and function of macrophages in normal pregnancy and in pregnancy complications. We mainly focused on the significant roles of decidual macrophages in the process of extravillous trophoblast invasion, spiral arterial remodeling, decidual stromal cells cultivation and immune tolerance maintenance in normal pregnancy, and their pathological roles in pregnancy-related complications, offering more integrated information in maternal-fetal immunity.